Traffic signatures in suspended dust at pedestrian levels in semiarid zones: Implications for human exposure. (August 2016) - Meza-Figueroa, Diana; González-Grijalva, Belem; Del Río-Salas, Rafael; Coimbra, Rute; Ochoa-Landin, Lucas; Moreno-Rodríguez, Verónica
Abstract: Deeper knowledge on dust suspension processes along semiarid zones is critical for understanding potential impacts on human health. Hermosillo city, located in the heart of the Sonoran Desert was chosen to evaluate such impacts. A one-year survey of Total Suspended Particulate Matter (TSPM) was conducted at two different heights (pedestrian and rooftop level). The minimum values of TSPM were reported during monsoon season and winter. Maximum values showed a bimodal distribution, with major peaks associated with increase and decrease of temperature, as well as decreasing humidity. Concentrations of TSPM were significantly exceeded at pedestrian level (∼44% of analyzed days) when compared to roof level (∼18% of analyzed days). Metal concentrations of As, Pb, Cu, Sb, Be, Mg, Ni, and Co were higher at pedestrian level than at roof level. Pixel counting and interpretations based on scanning electron microscopy of dust filters showed a higher percentage of fine particulate fractions at pedestrian level. These fractions occur mainly as metal-enriched agglomerates resembling coarser particles. According to worldwide guidelines, particulate matter sampling should be conducted by monitoring particle sizes equal and inferior to PM10 . However, this work suggests that such procedures may compromise risk assessment in semiarid environments, where coarse particles act as main carriers for emergent contaminants related to traffic. This effect is especially concerning at pedestrian level, leading to an underestimation of potential impacts of human exposure. This study brings forward novel aspects that are of relevance for those concerned with dust suspension processes across semiarid regions and related impact on human health. Highlights: Dust suspension of coarse particles affecting pedestrian. Pixel counting showing metal-enriched agglomerates. Coarse particles act as main carriers for emergent pollutants. Traffic geochemical signatures dominate dust at pedestrian level. Underestimation of human health impact by dust suspension.